Methodology for the creation of an entrepreneurial web-based quality management support service for the ISO 9001:2008 standard, which will provide a collaborative environment between quality certification professionals and hotel companies wishing to achie - Villacis Vargas, Jaime Fernando; Murillo Murillo, Xavier Dennis (Ingeniería Química y Desarrollo, 2024)
In this research, we proposed the design of an innovative support project for Ecuadorian hotel companies wishing to be certified under the ISO-9001:2008 standard through the use of one of the most successful ICT tools, the Internet, as a collaborative platform for quality management. A collaborative environment is sketched out between Ecuadorian hotel companies and professionals in the quality area. The beneficiaries of this project are: the hotel companies as such, since they would have a collaborative tool to achieve quality certification; the professionals in the area of quality management who would be the managers of change in the certifying companies being these placed through the proposed tool that outlines an environment of communication between companies and professionals in the area of quality in order to create sources of economic income through the placement and insertion of these in the possible certification projects. The Guayaquil hotel sector was chosen as a specific market, with which the project would start successfully. Based on the study conducted, it was shown that this project is welcomed by the respondents and therefore the conceptual design of the site www.certificatuhotel.com.ec was proposed, which outlines the solution to the problem presented in this study by offering a portal of good practices for the improvement of quality management oriented to the ISO 9001:2008 standard. The proposed site also provides information free of charge for visitors in general and access to the best practices tools will be for subscribers. The technological services platform on the Internet has a very favorable impact on improving quality management.